Analysis of Factors Affecting the Number of Poor People in South Tapanuli Regency, North Sumatra 2010-2022 - Haddad Alwi; Batubara, Ade Andriani (Outline Journal of Economic Studies, 2024)
This study aims to look at the factors that influence the number of poor people in South Tapanuli Regency. The data used is secondary data obtained through the Central Bureau of Statistics for North Sumatra Province. The data taken is the number of poor people (Y), the Human Development Index (X1), the total population (X2), and life expectancy (X3) with the observation year 2010-2022. The analytical model used in this study is multiple linear regression. The results of the analysis show that the Human Development Index (X1) and life expectancy (X3) have a negative and significant effect on the number of poor people in South Tapanuli Regency. While the population has a positive but not significant effect on the number of poor people in South Tapanuli Regency. The acquisition of an R-squared value of 0.855797 indicates that the Human Development Index (X1), population (X2), and life expectancy (X3) can simultaneously explain the poverty variable in Kab. South Tapanuli in 2010-2022 amounted to 85.5797% while the remaining 14.4203% is explained by other variables not included in this study.